Registro eletrônico de saúde baseado em software livre e integrado a sistemas de apoio ao diagnóstico - Valente, Igor Rafael Silva (2010)
The management and use of information and knowledge are the core of professional activities and decision-making in health practice. Health records, among which the most important is the patient's chart until recently were represented by paper documents kept in a variety of formats, content and locations. The inability to access and integrate data from individual patients or groups of patients enrolled in manual documents results in a fragmented view of the evolution of a community's health problems. The Electronic Health Record is the solution to many problems in this scenario. This project aims to develop an Electronic Health Record, web and free software based, ensuring data integrity, standardization, diagnostic support integration, innovation and easy usage.